(untitled) (2014)
Among orchids, vanilla is the only species that is an edible product. Its farming is being promoted in Colombia as an alternative to traditional crops, especially among small and medium farmers. Existing crops have a limited genetic base and are therefore susceptible to biotic stress, particularly those caused by viruses and fungi. Wild vanilla can be a source of variability that could help increase its gene pool and could also provide naturally associated endophyte microorganisms with antagonistic properties to fight pathogens of farmed vanilla. In this study we assessed the understanding of vanilla cultivation as well as the diversity of the genus Vanilla in Colombia. As a result of this first phase of research, we found twenty species of Colombian vanilla and 60 morphospecies of endophytic microorganisms. We discuss the relevance of these findings and their potential impact on promoting vanilla farming, and also discussed the use of these plants as a model group for basic research.